Cobalt-based bimetallic oxide, preparation method and application thereof, and electrode material
By ball milling the non-cobalt metal source and cobalt trioxide under supercritical carbon dioxide conditions, the existing cobalt-based bimetallic oxide preparation methods are solved, and an efficient and simplified preparation process is achieved. and high-performance cobalt-based bimetallic oxide electrode materials.
Patent Information
- Application Number
- CN202411366512.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The existing cobalt-based bimetal oxide preparation methods have complex processes, small output, high cost, and poor performance of the products, making it difficult to meet the needs of industrial applications.
Cobalt-based bimetal oxide was obtained by mixing a non-cobalt metal source with cobalt trioxide and ball milling under supercritical carbon dioxide conditions. This method simplifies the preparation process and avoids the use of high-temperature calcination and flammable and harmful substances.
The efficient preparation of cobalt-based bimetallic oxide is achieved. The obtained product is a single spinel phase, the mass specific capacity of the electrode reaches 963F/g, and the performance is significantly improved. It is suitable for applications such as supercapacitors.
Smart Images

Figure CN119430302A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material preparation, and in particular to a cobalt-based bimetallic oxide and a preparation method and application thereof. Background Art
[0002] Cobalt-based bimetallic oxides, such as nickel cobaltate, magnesium cobaltate, zinc cobaltate, copper cobaltate, etc., are spinel-type binary oxides, and their crystal structure belongs to the cubic system. In this structure, cobalt ions occupy the lattice sites of regular tetrahedrons, and another divalent metal occupies the regular octahedron sites. Cobalt-based bimetallic oxides have the characteristics of high conductivity, wide band gap, and high theoretical capacitance, and have broad application prospects in energy storage and conversion fields such as supercapacitors, magnesium ion batteries, photoelectric water splitting, electrocatalytic oxygen evolution reaction, and fuel cells.
[0003] However, the existing cobalt-based bimetallic oxide preparation method has a complex process, low yield, high cost, and poor product performance, which is difficult to meet the needs of industrial application of cobalt-based bimetallic oxide. For example, the Chinese patent with publication number CN112939097A discloses a cobalt-based nickel nanomaterial and its preparation method and application. The method prepares the cobalt-based nickel nanomaterial by high-temperature solvent thermal reaction and subsequent high-temperature calcination, but the single batch yield of the method is low, less than 0.05g, and it is difficult to achieve large-scale preparation of cobalt-based bimetallic oxide. Wang et al. (Journal of Nanoparticle Research 2015, 13, 339-349) prepared magnesium cobaltate nanowires by hydrothermal deposition and high-temperature calcination. The method not only requires high-temperature calcination, but also uses flammable and harmful hexamethylenetetramine as a structural synthesis agent, which limits the large-scale application of cobalt-based bimetallic oxide. In addition, Wang et al. (J Alloys Compd 2015, 688, 933-938) used a solvothermal method to prepare a magnesium cobalt oxide electrode material, but its electrochemical performance was relatively low, only 340 F / g, and the supercapacitor prepared based on this material could not meet the needs of practical applications. Summary of the invention
[0004] The object of the present invention is to provide a cobalt-based bimetallic oxide and a preparation method and application thereof. The preparation method provided by the present invention is simple, and the obtained cobalt-based bimetallic oxide is used to prepare an electrode, which can make the electrode have a higher mass specific capacity.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The invention provides a method for preparing a cobalt-based bimetallic oxide, comprising: mixing a non-cobalt metal source with cobalt trioxide and then ball milling the mixture under supercritical carbon dioxide conditions to obtain the cobalt-based bimetallic oxide; the non-cobalt metal source is an alkali or salt containing a non-cobalt metal; and the ball milling time is more than 8 hours.
[0007] Preferably, the non-cobalt metal-containing salt is a carbonate.
[0008] Preferably, the molar ratio of the non-cobalt metal source to cobalt trioxide is 1:1.
[0009] Preferably, the temperature of the supercritical carbon dioxide condition is 35-80° C., and the pressure of the supercritical carbon dioxide condition is 8-20 MPa.
[0010] Preferably, the ball milling time is 8 to 48 hours.
[0011] Preferably, the rotation speed of the ball mill is 100-800 rpm.
[0012] Preferably, the ball-to-material ratio of the ball mill is (5-20):1.
[0013] The present invention also provides a cobalt-based bimetallic oxide prepared by the preparation method described in the above technical solution, wherein the cobalt-based bimetallic oxide is a single spinel phase.
[0014] The present invention also provides the application of the cobalt-based bimetallic oxide described in the above technical solution.
[0015] The present invention also provides an electrode material comprising the cobalt-based bimetallic oxide described in the above technical solution.
[0016] The present invention provides a method for preparing a cobalt-based bimetallic oxide, comprising: mixing a non-cobalt metal source with cobalt trioxide and then ball milling under supercritical carbon dioxide conditions to obtain a cobalt-based bimetallic oxide; the non-cobalt metal source is an alkali or salt containing a non-cobalt metal; the ball milling time is more than 8 hours. The present invention uses an alkali or salt containing a non-cobalt metal and cobalt trioxide as raw materials, and ball milling under supercritical carbon dioxide conditions. Under the collision, extrusion, impact and shearing of the ball milling jar and the ball milling beads, the ionic bonds of the raw materials are broken and reorganized to obtain a cobalt-based bimetallic oxide; by changing the pressure and temperature of the supercritical carbon dioxide, the properties of the reaction system can be adjusted, such as changing the density, etc., to avoid agglomeration of the reactants, improve the energy efficiency of the reaction, and then reduce the impurities in the crystal phase structure of the product, improve the purity of the product, and further improve the electrochemical performance of the product. The results of the embodiment show that the preparation method provided by the present invention only needs to perform a ball milling reaction step, and there is no post-treatment process such as calcination; and a single spinel phase cobalt-based bimetallic oxide is prepared, which is used to prepare an electrode, and the mass specific capacity of the electrode reaches 963F / g. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a macroscopic photograph of the cobalt-based bimetallic oxide prepared in Example 1;
[0018] Figure 2 is the X-ray diffraction pattern of the cobalt-based bimetallic oxide prepared in Example 1;
[0019] Figure 3 The figure is a charge and discharge test result diagram of an electrode including the cobalt-based bimetallic oxide prepared in Example 1;
[0020] Figure 4 is the X-ray diffraction pattern of the cobalt-based bimetallic oxide prepared in Example 2;
[0021] Figure 5 is the X-ray diffraction pattern of the cobalt-based bimetallic oxide prepared in Example 3;
[0022] Figure 6 This is a macroscopic photograph of the cobalt-based bimetallic oxide prepared in Comparative Example 1;
[0023] Figure 7 The X-ray diffraction pattern of the powder prepared in Comparative Example 1;
[0024] Figure 8 The X-ray diffraction pattern of the powder prepared in Comparative Example 2;
[0025] Fig. 9 This is the X-ray diffraction pattern of the powder prepared in Comparative Example 3. DETAILED DESCRIPTION
[0026] All raw materials of the present invention have no particular limitation on their sources and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0027] There is no particular limitation on the purity of all raw materials in the present invention. The present invention preferably uses analytically pure materials or materials with conventional purity in the field of material preparation.
[0028] The invention provides a method for preparing a cobalt-based bimetallic oxide, comprising: mixing a non-cobalt metal source with cobalt trioxide and then ball milling the mixture under supercritical carbon dioxide conditions to obtain the cobalt-based bimetallic oxide.
[0029] In the present invention, the non-cobalt metal source is an alkali or salt containing a non-cobalt metal, preferably an alkali containing a non-cobalt metal; the salt containing a non-cobalt metal is preferably a carbonate. In an embodiment of the present invention, the non-cobalt metal source can be magnesium hydroxide, nickel hydroxide, zinc hydroxide, copper hydroxide, magnesium carbonate, nickel carbonate, zinc carbonate or copper carbonate. The molecular structure of the above non-cobalt metal sources contains ionic bonds, which can be broken by ball milling and react with cobalt trioxide to obtain a cobalt-based bimetallic oxide.
[0030] In the present invention, the molar ratio of the non-cobalt metal source to cobalt trioxide is preferably 1:1. A suitable molar ratio is conducive to the synthesis of magnesium cobaltate material with a purity of 100%.
[0031] In the present invention, as an embodiment, the temperature of the supercritical carbon dioxide condition can be 35-80° C., or 35-50° C.; in an embodiment of the present invention, the temperature of the supercritical carbon dioxide condition can be specifically 35° C., 37° C., 40° C., 42° C., 45° C., 47° C., or 50° C. The temperature of the supercritical carbon dioxide condition is within the above range, which can ensure that the carbon dioxide is in a supercritical state without excessive energy consumption.
[0032] In the present invention, as an embodiment, the pressure of the supercritical carbon dioxide condition can be 8-20MPa, or 8-15MPa; in an embodiment of the present invention, the pressure of the supercritical carbon dioxide condition can be specifically 8MPa, 9MPa, 10MPa, 11MPa, 12MPa, 13MPa, 14MPa, 15MPa. The pressure of the supercritical carbon dioxide condition is within the above range, which can ensure that the carbon dioxide is in a supercritical state and has low requirements on equipment.
[0033] In the present invention, the ball milling time is more than 8 hours. As an embodiment of the present invention, the ball milling time can be 8 to 48 hours, or 8 to 24 hours. In an embodiment of the present invention, the ball milling time can be specifically 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, and 24 hours. The ball milling time directly affects the progress of the reaction. If the ball milling time is too short, the reaction is incomplete, which wastes resources and affects the quality of the product. If the ball milling time is too long, the production cycle will be extended and the production efficiency will be affected. The ball milling time is within the above range, which can ensure that the reaction is completely carried out and has good production efficiency.
[0034] In the present invention, as an embodiment, the rotation speed of the ball mill can be 100-800rpm, or 250-350rpm. The rotation speed of the ball mill affects the effect and efficiency of the ball mill. If the rotation speed is too low, the ball mill cannot achieve the expected effect, or the ball milling time needs to be extended; if the rotation speed is too fast, the material may be ground unevenly and the equipment loss may be increased. When the rotation speed of the ball mill is within the above range, the material can be effectively ground, which is beneficial to improving the reaction efficiency.
[0035] In the present invention, as an embodiment, the ball milling beads of the ball milling can be one or more of stainless steel balls, zirconium oxide, aluminum oxide and agate; the diameter of the ball milling beads can be 1-5 mm; the ball-to-material ratio of the ball milling can be (5-20):1, or (8-15):1. The ball-to-material ratio will affect the efficiency of the reaction. Too few ball milling beads will lead to insufficient reaction, and too many ball milling beads will reduce energy efficiency. When the ball-to-material ratio is within the above range, the ball milling can be effectively carried out to allow the reaction to proceed normally.
[0036] After the ball milling is completed, the present invention preferably releases the carbon dioxide in the ball mill kettle for recovery, and then separates the material and the ball milling beads to obtain the cobalt-based bimetallic oxide.
[0037] In the present invention, the separation is preferably performed by sieve separation, and the mesh number of the sieve is preferably 20 to 100 meshes.
[0038] The invention uses cobalt trioxide and a non-cobalt metal source as raw materials, and ball mills them under supercritical carbon dioxide conditions. Under the collision, extrusion, impact and shearing of the ball mill and the ball mill beads, the ionic bonds of the raw materials are broken and reorganized to obtain cobalt-based bimetallic oxides. The pressure and temperature of the supercritical carbon dioxide can be used to adjust the properties of the reaction system, such as changing the density, etc., to avoid agglomeration of reactants, improve the energy efficiency of the reaction, reduce impurities in the crystal phase structure of the product, and improve the purity of the product.
[0039] The present invention also provides a cobalt-based bimetallic oxide prepared by the preparation method described in the above technical solution, wherein the cobalt-based bimetallic oxide is a single spinel phase.
[0040] The present invention also provides the application of the cobalt-based bimetallic oxide described in the above technical solution. The present invention has no special limitation on the application method, and the application method of the cobalt-based bimetallic oxide well known to those skilled in the art can be adopted.
[0041] The present invention also provides an electrode material comprising the cobalt-based bimetallic oxide described in the above technical solution. As one embodiment of the present invention, the cobalt-based bimetallic oxide as an active component of the electrode material is mixed with a conductive agent, a binder and a solvent and then coated on an electrode sheet to prepare an electrode.
[0042] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] Example 1
[0044] A cobalt-based bimetallic oxide, the preparation method is as follows:
[0045] Take 74g of cobalt trioxide and 26g of magnesium hydroxide (molar ratio of 1:1) and add them into a stainless steel ball mill with a volume of 1L, add 1000g of zirconium oxide ball milling beads (diameter of 1mm); tighten the lid of the kettle by tightening the screws until it is sealed, fill it with 350g of carbon dioxide and put the ball mill into the ball mill; adjust the ball mill speed to 350rpm, the temperature in the ball mill to 35℃, and the pressure in the ball mill to 10MPa. After ball milling for 8h, release the carbon dioxide gas, open the lid of the ball mill, and observe the product state, such as Figure 1 As shown, according to Figure 1 It can be seen that the product is a fluffy black powder. The reaction product and ball mill beads were taken out and separated through a sieve (50 mesh) to obtain a cobalt-based bimetallic oxide, a total of 99g, with a yield of 99% (powder mass after reaction / powder mass before reaction).
[0046] The cobalt-based bimetallic oxide was characterized by an X-ray diffractometer. The analytical instrument was RigakuMini Flex600 and the scanning rate was 10° / min. The results are as follows: Figure 2 As shown, from Figure 2 It can be seen that the cobalt-based bimetallic oxide prepared in Example 1 is magnesium cobaltate of a single spinel phase, indicating that the non-cobalt metal source is completely reacted and the reaction conversion rate (100% - mass of non-cobalt metal source after reaction / mass of non-cobalt metal source before reaction) reaches 100%.
[0047] The cobalt-based bimetallic oxide prepared in Example 1 was subjected to an electrochemical performance test. The specific method is as follows: the prepared cobalt-based bimetallic oxide, conductive agent, and adhesive were mixed in N-methylpyrrolidone at a ratio of 80:15:5, coated on the cleaned nickel foam, and dried as a working electrode. The electrochemical performance test was carried out using a three-electrode system, with a mercury oxide electrode as the reference electrode and a platinum wire as the counter electrode; the electrolyte solution was a 3 mol / L potassium hydroxide solution; the charge and discharge voltage range was 0.1 to 0.5 V, and the current density was 0.1 A / g. The results are as follows: Figure 3 As shown. Figure 3It can be seen that the mass specific capacitance of the electrode is as high as 963F / g, and it has good electrochemical performance, indicating that the cobalt-based bimetallic oxide prepared by the present invention can be used as an electrode material in supercapacitors.
[0048] Example 2
[0049] A cobalt-based bimetallic oxide, the preparation method is as follows:
[0050] Take 64g of cobalt trioxide and 36g of nickel hydroxide (molar ratio of 1:1) and add them to a stainless steel ball mill with a volume of 1L, add 1000g of zirconium oxide ball milling beads (diameter of 1mm); tighten the lid of the kettle by tightening the screws until it is sealed, fill it with 350g of carbon dioxide and put the ball mill into the ball mill; adjust the ball mill speed to 350rpm, the temperature in the ball mill to 35℃, and the pressure in the ball mill to 10MPa. After ball milling for 24h, release the carbon dioxide gas, open the ball mill lid, and observe that the product is a fluffy black powder. Take out the reaction product and ball milling beads, separate them through a sieve (50 mesh), and obtain a cobalt-based bimetallic oxide, a total of 99g, with a yield of 99%.
[0051] The cobalt-based bimetallic oxide was characterized by an X-ray diffractometer. The analytical instrument was RigakuMini Flex600 and the scanning rate was 10° / min. The results are as follows: Figure 4 As shown, from Figure 4 It can be seen that the cobalt-based bimetallic oxide prepared in Example 2 is nickel cobaltate of a single spinel phase, indicating that the reaction conversion rate reaches 100%.
[0052] Example 3
[0053] A cobalt-based bimetallic oxide, the preparation method is as follows:
[0054] Take 66g of cobalt trioxide and 34g of magnesium carbonate (molar ratio of 1:1) and add them to a stainless steel ball mill with a volume of 1L, add 1000g of zirconium oxide ball milling beads (diameter of 1mm); tighten the lid of the kettle by tightening the screws until it is sealed, fill it with 150g of carbon dioxide and put the ball mill into the ball mill; adjust the ball mill speed to 350rpm, the temperature in the ball mill to 35℃, and the pressure in the ball mill to 8MPa. After ball milling for 24h, release the carbon dioxide gas, open the ball mill lid, and observe that the product is a fluffy black powder. Take out the reaction product and ball milling beads, separate them through a sieve (50 mesh), and obtain a cobalt-based bimetallic oxide, a total of 99g, with a yield of 99%.
[0055] The cobalt-based bimetallic oxide was characterized by an X-ray diffractometer. The analytical instrument was RigakuMini Flex600 and the scanning rate was 10° / min. The results are as follows: Figure 5 As shown, from Figure 5It can be seen that the cobalt-based bimetallic oxide prepared in Example 3 is magnesium cobaltate in a single spinel phase, indicating that the reaction conversion rate is as high as 100%.
[0056] Comparative Example 1
[0057] The preparation was carried out in the manner of Example 1, except that no carbon dioxide was added during the ball milling process, specifically:
[0058] Take 74g of cobalt trioxide and 26g of magnesium hydroxide (molar ratio of 1:1) and add them into a stainless steel ball mill with a volume of 1L, and add 1000g of zirconium oxide ball milling beads (diameter of 1mm); tighten the lid of the kettle by tightening the screws until it is sealed, and then put the ball mill into the ball mill; adjust the ball mill speed to 350rpm and the temperature in the ball mill to 35℃. After ball milling for 8h, open the lid of the ball mill and observe the product state, such as Figure 6 As shown, from Figure 6 It can be seen that the product is obviously solidified at the bottom of the ball mill. After the unsolidified powder is separated from the ball mill beads through a sieve (50 mesh), a total of 15g of product is obtained, with a yield of only 15%. Since the material is obviously solidified, the yield of the product is seriously affected.
[0059] The obtained product was characterized by an X-ray diffractometer, the analytical instrument was Rigaku Mini Flex 600, and the scanning rate was 10° / min. The results are shown in Figure 7 As shown, from Figure 7 It can be seen that the product obtained in Comparative Example 1 has an obvious impurity phase, and the impurity is the reactant magnesium hydroxide, and the content of magnesium hydroxide reaches 16.5wt%, and the reaction conversion rate calculated accordingly is only 63.5%. By comparing Example 1 with Comparative Example 1, it is shown that the present invention not only has a high conversion rate and obtains a single spinel phase product; but also has a high yield, which is conducive to industrial promotion.
[0060] Comparative Example 2
[0061] The preparation was carried out in the manner of Example 1, except that the ball milling time was reduced to 4 h, specifically:
[0062] Take 74g of cobalt trioxide and 26g of magnesium hydroxide (molar ratio of 1:1) and add them to a stainless steel ball mill with a volume of 1L, and add 1000g of zirconia ball milling beads (diameter of 1mm); tighten the kettle cover by tightening the screws until it is sealed, fill it with 350g of carbon dioxide and put the ball mill into the ball mill; adjust the ball mill speed to 350rpm, the temperature in the ball mill to 35°C, and the pressure in the ball mill to 10MPa. After ball milling for 4h, release carbon dioxide gas, release carbon dioxide gas, and observe that the product is a fluffy black powder; take out the reaction product and ball milling beads, separate them through a sieve (50 mesh), and obtain the reacted product.
[0063] The obtained product was characterized by an X-ray diffractometer, the analytical instrument was Rigaku Mini Flex 600, and the scanning rate was 10° / min. The results are shown in Figure 8 As shown, from Figure 8 It can be seen that the product obtained in Comparative Example 2 has an obvious impurity phase, and the impurity is the reactant magnesium hydroxide, with a content of 3.8wt%. Based on this calculation, the conversion rate of the reaction is 85.4%.
[0064] Comparative Example 3
[0065] The preparation was carried out in the manner of Example 1, except that the reactant was changed from hydroxide to oxide, specifically:
[0066] Take 80g of cobalt trioxide and 20g of magnesium oxide (molar ratio of 1:1) and add them to a stainless steel ball mill with a volume of 1L, and add 1000g of zirconium oxide ball milling beads (diameter of 1mm); tighten the lid of the kettle by tightening the screws until it is sealed, fill it with 350g of carbon dioxide and put the ball mill into the ball mill; adjust the ball mill speed to 350rpm, the temperature in the ball mill to 35°C, and the pressure in the ball mill to 10MPa. After ball milling for 8h, release carbon dioxide gas and observe that the product is a fluffy black powder; take out the reaction product and ball milling beads, separate them through a sieve (50 mesh), and obtain the reacted product.
[0067] The obtained product was characterized by an X-ray diffractometer, the analytical instrument was Rigaku Mini Flex 600, and the scanning rate was 10° / min. The results are shown in Fig. 9 As shown, from Fig. 9 It can be seen that the product obtained in Comparative Example 3 has obvious impurity phase, the impurity is the reactant magnesium oxide, and the content is 19.0wt%, and the reaction conversion rate is only 5%. This is because the Mg-O bond in magnesium oxide is a covalent bond, while the Mg-(OH) bond in magnesium hydroxide is an ionic bond; in the ball milling reaction, the covalent bond is more difficult to break than the ionic bond, indicating that the type of reactant metal raw material has a significant impact on the reaction process.
[0068] It can be seen from the above embodiments and comparative examples that the present invention uses cobalt trioxide and a non-cobalt metal source as raw materials, and ball mills them under supercritical carbon dioxide conditions. By limiting the type of raw materials and controlling the ball milling time, a single spinel phase cobalt-based bimetallic oxide can be obtained for preparing an electrode. The mass specific capacity of the electrode reaches 963F / g, which can be used in supercapacitors.
[0069] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a cobalt-based bimetallic oxide, characterized in that: include: A non-cobalt metal source is mixed with cobalt trioxide and then ball-milled under supercritical carbon dioxide conditions to obtain a cobalt-based bimetallic oxide; the non-cobalt metal source is an alkali or salt containing a non-cobalt metal; and the ball-milling time is more than 8 hours.
2. The preparation method according to claim 1, characterized in that: The non-cobalt metal-containing salt is a carbonate.
3. The preparation method according to claim 1 or 2, characterized in that: The molar ratio of the non-cobalt metal source to cobalt trioxide is 1:
1.
4. The preparation method according to claim 1, characterized in that: The temperature of the supercritical carbon dioxide condition is 35-80° C., and the pressure of the supercritical carbon dioxide condition is 8-20 MPa.
5. The preparation method according to claim 1, characterized in that: The ball milling time is 8 to 48 hours.
6. The preparation method according to claim 1, characterized in that: The rotation speed of the ball mill is 100-800 rpm.
7. The preparation method according to claim 1, 5 or 6, characterized in that: The ball-to-material ratio of the ball mill is (5-20):
1.
8. The cobalt-based bimetallic oxide prepared by the preparation method according to any one of claims 1 to 7, wherein the cobalt-based bimetallic oxide is a single spinel phase.
9. Use of the cobalt-based bimetallic oxide according to claim 8.
10. An electrode material comprising the cobalt-based bimetallic oxide according to claim 8.
Citation Information
Patent Citations
Nickel cobaltate nano material as well as preparation method and application thereof
CN112939097A
Method for preparing metal organic framework molecular sieve membrane by supercritical fluid technology
CN111589311A
Waste textile metal nanoparticle composite carbon fiber aerogel and preparation method thereof
CN112426979A
Nickel-cobalt bimetallic oxide as well as preparation method and application thereof
CN112830528A
Metal-organic framework-based composite electrolyte for lithium metal battery
CN113130985A